Nanomaterials for Cardiac Tissue Engineering Application - Zhang, Yachen; Tang, Yong; Wang, Ying; Zhang, Liying (Nano-Micro Letters, 2011)
In recent years, the emerging cardiac tissue engineering provides a new therapeutic method for heart diseases. And in the tissue engineering, the scaffold material which can mimic the structure of the extracellular matrix properly is a key factor. The rapid expansion of nano-scaffolds during the past ten years has led to new perspectives and advances in biomedical research as well as in clinical practice. Here we search articles published in recent years extensively on cardiac tissue engineering scaffold materials and nanotechnology. And we review the traditional scaffold materials and the advances of the nano-scaffolds in cardiac tissue engineering. A thorough understanding of the nano-scaffolds would enable us to better exploit technologies to research the ideal scaffold material, and promote the cardiac tissue engineering using in the clinical practice as soon as possible.